Sex effects on early life features of the gingival transcriptome - Ebersole, J. L.; Kirakodu, S. S.; Nguyen, L. M.; Gonzalez, O. A. (Frontiers in Dental Medicine, 2025)
BackgroundEpidemiologic assessment of periodontitis prevalence and extent demonstrates age, sex, and race/ethnicity effects. However, the biological sources of these observations regarding sex differences with an elevated incidence in males remain unclear.MethodsThis study used a model of experimental ligature-induced periodontitis in young nonhuman primates (Macaca mulatta) to evaluate gingival transcriptomic differences stratified based on the sex of the animal. The animals represent humans aged 10–25 years of age, with gingival tissue samples obtained at baseline, 0.5 months (initiation), and 1 and 3 months (progression). Microarray analysis was used to quantify gene expression profiles in the gingival tissues.ResultsThe results demonstrated clear gene expression differences in healthy (baseline) tissues between the sexes, with elevations in females associated with immune responses and elevated gene expression in males related to tissue structural genes. With disease initiation, fewer genes differed between the sexes, although a pattern of a greater number of unique gene expression changes was observed in females at late progression. Overexpressed biological processes showed tissue structural/functional genes at initiation, with host response pathways altered during disease progression.ConclusionThese findings support that this model can be used to explore processes that contribute to sex as a biological variable in periodontitis.